1999
DOI: 10.1007/s004240050817
|View full text |Cite
|
Sign up to set email alerts
|

Activation of wild-type and ΔF508-CFTR by phosphodiesterase inhibitors through cAMP-dependent and -independent mechanisms

Abstract: The cAMP-dependent activation of the cystic fibrosis transmembrane conductance regulator (CFTR) and its modulation through inhibition of phosphodiesterases (PDE) were studied with the cell-attached patch-clamp technique in Calu-3 cells (expressing endogenous CFTR) and NIH3T3 cells [expressing either wild-type (Wt)-CFTR or DeltaF508-CFTR]. In Calu-3 cells, CFTR current was augmented by increasing concentrations of 8-(4-chlorophenylthio)-adenosine 3', 5'-cyclic monophosphate (CPT-cAMP) and reached a saturating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…A number of biochemical and electrophysiological studies have clearly shown that DF508CFTR rescued at the plasma membrane by a number of different methods, including growth at low temperature (Denning et al, 1992) and treatment with chemical chaperons or inhibitors of protein degradation, still exhibits additional defects that limit ion transport, including reduced channel gating (Al-Nakkash and Hwang, 1999;Hwang et al, 1997;Wang et al, 1998). However, studies in cell-free systems and on isolated protein have shown that DF508CFTR retains normal PKAdependent regulation and activity relative to wt CFTR (Li et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A number of biochemical and electrophysiological studies have clearly shown that DF508CFTR rescued at the plasma membrane by a number of different methods, including growth at low temperature (Denning et al, 1992) and treatment with chemical chaperons or inhibitors of protein degradation, still exhibits additional defects that limit ion transport, including reduced channel gating (Al-Nakkash and Hwang, 1999;Hwang et al, 1997;Wang et al, 1998). However, studies in cell-free systems and on isolated protein have shown that DF508CFTR retains normal PKAdependent regulation and activity relative to wt CFTR (Li et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A potential advantage of pharmacotherapy for defective ∆F508-CFTR processing and gating is that it minimizes concerns about treating the wrong cells or losing physiological CFTR regulation, as might occur with gene therapy or activation of alternative chloride channels. Small-molecule ∆F508-CFTR potentiators with relatively low potency (>10-50 µM) have been characterized, including the flavone genistein and the xanthine isobutylmethylxanthine (14)(15)(16)(17). Recently, our laboratory identified by high-throughput screening tetrahydrobenzothiophene, phenylglycine, and sulfonamide potentiators that correct defective ∆F508-CFTR gating at concentrations below 100 nM by a mechanism involving increased channel open time (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Calu-3 cells produce several serous cell-associated proteins including lysozyme, lactoferrin, serine leukoprotease inhibitor (SLP1), secretory component, and mucins (MUC1 and MUC2) (Finkbeiner et al 1993). The Calu-3 cells are now used by many laboratories as a serous cell model (Kelley et al 1995;Grygorczyk et al 1997;Liedtke et al 1998;Al-Nakkash et al 1999;Berger et al 1999;Duszyk et al 1999;Illek et al 1999;Ito et al 1999;Waters et al 1999). Our studies on Calu-3 cells showed that they secrete HCO 3 2 rather than Cl 2 in response to cAMP-mediated agonists.…”
Section: Studies With Calu-3 Cellsmentioning
confidence: 60%